Early prenatal sonographic diagnosis and follow‐up of Jeune syndrome - Den Hollander, N. S.; Robben, S. G. F.; Hoogeboom, A. J. M.; Niermeijer, M. F.; Wladimiroff, J. W. (Ultrasound in obstetrics & gynecology, 2001)
Jeune syndrome or asphyxiating thoracic dysplasia is an autosomal recessive osteochondrodysplasia. It is one of the six short‐rib (polydactyly) syndromes. The disease has a wide spectrum of manifestations, ranging from a latent to a mild or lethal condition. We describe the prenatal sonographic diagnosis of Jeune syndrome at 14 weeks of gestation in a fetus at risk for this condition, and the development of the syndrome throughout the pregnancy. Copyright © 2001 International Society of Ultrasound in Obstetrics and Gynecology